2001
DOI: 10.1126/science.1057110
|View full text |Cite
|
Sign up to set email alerts
|

Living with Genome Instability: Plant Responses to Telomere Dysfunction

Abstract: Loss of telomere function in metazoans results in catastrophic damage to the genome, cell cycle arrest, and apoptosis. Here we show that the mustard weed Arabidopsis thaliana can survive up to 10 generations without telomerase. The last five generations of telomerase-deficient plants endured increasing levels of cytogenetic damage, which was correlated with developmental anomalies in both vegetative and reproductive organs. Mutants ultimately arrested at a terminal vegetative state harboring shoot meristems th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
258
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(279 citation statements)
references
References 30 publications
21
258
0
Order By: Relevance
“…Insufficient or defects in telomerase activity in stem cell compartment provoke telomere shortening that results in loss of cells and in tissue dysfunction [58]. Interestingly, regardless of the telomere length in species, knocking out of telomerase in mice, Caenorhabditis elgans and plants such as Arabidopsis results in reproduction failure after several generations in addition to other abnormalities [59][60][61]. Recent studies have demonstrated a function of telomerase in activating stem cells through a mechanism that does not required telomerase activity.…”
Section: Telomerase In Stem Cellsmentioning
confidence: 99%
“…Insufficient or defects in telomerase activity in stem cell compartment provoke telomere shortening that results in loss of cells and in tissue dysfunction [58]. Interestingly, regardless of the telomere length in species, knocking out of telomerase in mice, Caenorhabditis elgans and plants such as Arabidopsis results in reproduction failure after several generations in addition to other abnormalities [59][60][61]. Recent studies have demonstrated a function of telomerase in activating stem cells through a mechanism that does not required telomerase activity.…”
Section: Telomerase In Stem Cellsmentioning
confidence: 99%
“…Beginning in the sixth generation (G6), tert mutants exhibit a low level of end-to-end chromosome fusions and the onset of growth and developmental defects (37). Remarkably, plants survive for up to five more generations with worsening phenotypes until they ultimately arrest growth in a miniature, dedifferentiated state, unable to produce a germ line (37).…”
mentioning
confidence: 99%
“…Telomeres are constructed with telomere repeats, as well as specific proteins (Cech 2004), and are important in controlling chromosome positions in the nucleus (Naito et al 1998, Riha et al 2001, Bechard et al 2009). Telomere repeats have been reported in many taxa.…”
mentioning
confidence: 99%